Evolution of practice nursing in Australia - Halcomb, E.; Patterson, E.; Davidson, Patricia (Wiley-Blackwell Publishing Ltd, 2006)
Aim. This paper describes the evolution of Australian practice nursing and documents seminal events in crystallizing the importance of the nursing role in general practice. Background. Internationally, the potential for nurses to improve health in primary care settings is acknowledged. The general practice setting is a focal point for primary care in many health systems. Despite the important role played in the delivery of primary health care by nurses working in general practice in the United Kingdom and New Zealand, the role of nurses in Australian general practice is much less clearly defined, as reflected by the paucity of research and scholarship in this area. Fuelled by the increasing challenges of workforce shortages and the increasing need for multidisciplinary care, interest in the developing role of the Australian practice nurse among clinicians, researchers and policy makers is increasing. Discussion. Australian practice nursing has reached a critical point in its evolution. It is imperative for the promotion of nursing in general practice that knowledge from descriptive, exploratory research be used to inform strategic decision-making in terms of professional development issues, policy, research and scholarship. These data also need to inform systematic outcome studies. To date, the embryonic nature of practice nursing as a discrete professional entity in Australia has inhibited its representation in nursing curricula and professional bodies. Conclusion. In order to advance the Australian practice nurse movement and demonstrate its important contribution to primary health care, nurses need to take the lead in strategic planning of this emerging specialty. As well as leadership from an academic, research and policy perspective, clinical leaders need to be fostered among the ranks of practice nurse clinicians to drive clinical practice development and the delivery of evidence-based primary care.